Final design and on-sky testing of the iLocater SX acquisition camera: broad-band single-mode fibre coupling. Issue 2 (30th October 2020) - Crass, J; Bechter, A; Sands, B; King, D; Ketterer, R; Engstrom, M; Hamper, R; Kopon, D; Smous, J; Crepp, J R; Montoya, M; Durney, O; et al.
ABSTRACT: Enabling efficient injection of light into single-mode fibres (SMFs) is a key requirement in realizing diffraction-limited astronomical spectroscopy on ground-based telescopes. SMF-fed spectrographs, facilitated by the use of adaptive optics (AO), offer distinct advantages over comparable seeing-limited designs, including higher spectral resolution within a compact and stable instrument volume, and a telescope independent spectrograph design. iLocater is an extremely precise radial velocity (EPRV) spectrograph being built for the Large Binocular Telescope (LBT). We have designed and built the front-end fibre injection system, or acquisition camera, for the SX (left) primary mirror of the LBT. The instrument was installed in 2019 and underwent on-sky commissioning and performance assessment. In this paper, we present the instrument requirements, acquisition camera design, as well as results from first-light measurements. Broad-band SMF coupling in excess of 35 per cent (absolute) in the near-infrared (0.97–1.31 ${μ {\rm m}}$ ) was achieved across a range of target magnitudes, spectral types, and observing conditions. Successful demonstration of on-sky performance represents both a major milestone in the development of iLocater and in making efficient ground-based SMF-fed astronomical instruments a reality.